Learning styles and learning behaviour in the hypermedia environment RACE - Analysing computer log files and questionnaire data - Thielke, S.; Rockmann, U.; Seyda, M. (International Journal of Computer Science in Sport, 2003)
The following Paper describes an experiment which analyses in how far specific learner types, set by questionnaire, show congruent behaviour in a concrete learning situation. The a priori subdivision into surface- and deep-strategy learner types is based on established models (Schmeck, 1988; Mandl & Friedrich, 1992; Krapp, 1993). First, a group of 52 learners worked with the hypermedia programme RACE (Rockmann & Thielke, 2000b, 2000a, 2001, 2002) for one hour. Then a general questionnaire about their learning behaviour in self-regulated learning situations was given. The questionnaire data (trait measurement) and the process data from the log files (state measurement) were evaluated by clusteranalysis and compared with each other. The experiment shows that both analyses result in a two-cluster solution with clear allocation of surface- and deep-strategy variables. The congruency between these solutions amounts to approx. 70%, and a significant difference could not be determined, X² (1, N = 50) = 0.581 (p =.446).The comparison of the z-transformed means for the cluster variables indicates that the analyses of the process data may be of a higher selectivity for determining these learning types. Interesting findings concerning the cluster composition can be shown when you include further descriptive variables (expertnovice status, state of training and computer experience).